Polariton‐Induced Enhanced Emission from an Organic Dye under the Strong Coupling Regime. Issue 11 (8th August 2014) - Ballarini, Dario; De Giorgi, Milena; Gambino, Salvatore; Lerario, Giovanni; Mazzeo, Marco; Genco, Armando; Accorsi, Gianluca; Giansante, Carlo; Colella, Silvia; D'Agostino, Stefania; Cazzato, Paolo; Sanvitto, Daniele; et al.
<x xml:space="preserve">Abstract</x> Exciton–polaritons in semiconductors are quasi‐particles which have recently shown the capability to undergo phase transition into a coherent hybrid state of light and matter. The observation of such quasi‐particles in organic microcavities has attracted increasing attention for their characteristic of reaching condensation at room temperature. In this work, the emission properties of organic polaritons are demonstrated not to depend on the overlap between the absorption and emission states of the molecule and that the emission dynamics are modified in the strong coupling regime, showing a significant enhancement of the photoluminescence intensity as compared to the bare dye. This paves the way to the investigation of molecules with large absorption coefficients but poor emission efficiencies for the realization of polariton condensates and organic electrically injected lasers by exploiting strong exciton‐photon coupling regimes.